Geophysical Subsurface Mapping Using the Electrical Resistivity Technique: A Comprehensive Study of the Petroleum Training Institute Main Campus in Effurun - Ojo, Odunayo Tope; Chiaka, Ike Joy; Mark, Ameh Igoche (MO.RI Publishing, 2024)
The electrical resistivity method was used to conduct a detailed examination of subsurface geology and hydrogeological parameters at the Petroleum Training Institute (PTI) Main Campus in Effurun, Nigeria. The research includes field data collecting, sounding curve interpretation, and dipole-dipole data processing. Both qualitative and quantitative methods were employed to gain a complete understanding of the hydrogeophysical features of the research area. The analysis revealed A and AK formations, which include four, five, and six-layer structures, highlighting the subsurface's intricacy. A frequency table was utilised to categorise the distribution of VES curves within the study area into three major groups. This classification was critical for characterising and comprehending the area's hydrogeological and geological complexity. Geo-electric sections were created to illustrate the different underlying layers, such as topsoil, clayey sand, sand, sandstone, and fracture. The study analyzed geoelectric properties and aquifer zones using resistivity isopach maps in 2D and 3D formats. The northeastern part of the study area had higher resistivity values, indicating geological variables affecting rock composition and groundwater supply. The findings are crucial for effective groundwater resource management, environmental assessments, and regional development planning. The geological model, combining data from dipole-dipole, geo-electric, and VES sections, accurately characterized subsurfaces in the PTI Campus area. The study identified six subsurface layers, providing baseline data for future infrastructure development. Recommendations include using advanced geophysical methods and a more detailed assessment of subsurface geology in the Warri region. This study adds to our understanding of the hydrogeological and geological aspects of the PTI Campus area, allowing us to make more informed judgements concerning environmental and infrastructure design. The study offers a comprehensive analysis of subsurface geology and hydrogeological parameters at PTI Main Campus, contributing valuable insights for groundwater management, environmental assessments, and regional development planning.